2012
DOI: 10.1016/s0019-4832(12)60047-9
|View full text |Cite
|
Sign up to set email alerts
|

A look into Lee's score: peri-operative cardiovascular risk assessment in non-cardiac surgeries—usefulness of revised cardiac risk index

Abstract: Objective: The revised cardiac risk index (RCRI/Lee's score) was designed for peri-operative risk assessment before elective major non-cardiac surgeries. Through this article, we report the usefulness of RCRI in our daily practice, while evaluating patients undergoing surgeries of varying risk.Methods: Only referred patients, aged ≥ 40 years, were included. Risk stratification was done using RCRI scoring system. Patients were categorised into 4 classes depending on 0, 1, 2, and ≥3 risk predictors (risk predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Romero-Corral et al 23 also reported that, in patients with coronary artery disease, those who were overweight (25–29.9 kg/m 2 ) had lower mortality. In line with previous studies, 14,24 preoperative hypertension, coronary heart disease, arrhythmia, and renal insufficiency were also associated with an increased risk of postoperative MACEs in our patients. Long-term glucocorticoid therapy increases the risk of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 93%
“…Romero-Corral et al 23 also reported that, in patients with coronary artery disease, those who were overweight (25–29.9 kg/m 2 ) had lower mortality. In line with previous studies, 14,24 preoperative hypertension, coronary heart disease, arrhythmia, and renal insufficiency were also associated with an increased risk of postoperative MACEs in our patients. Long-term glucocorticoid therapy increases the risk of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 93%
“…The RCRI aims to predict post-operative pulmonary edema, myocardial infarction, ventricular fibrillation or cardiac arrest, and complete heart block. The RCRI used to be considered a very useful cardiacrisk prediction index in noncardiac surgery; however, it was developed years ago and many progressions occurred since then regarding diagnosis and management of cardiovascular diseases [7].…”
Section: Risk Scoresmentioning
confidence: 99%
“…In clinical practice, risk scores are not implemented unanimously, also these scores should not impose a predetermined management decision systematically, they should rather be regarded as one of the multiple pieces of the puzzle in the pre-operative context. In addition, these risk scores were developed years ago, and none has a perfect predictive value; in this regard, they could be used as complementary risk predictors in a changing medical world [7], [8]. Moreover, they should be used to optimize the pre-operative risk stratification, helping to reduce unnecessary pre-operative paraclinical tests and to apply tailored perioperative management [8].…”
Section: Risk Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…The RCRI identifies patients at higher risk for cardiovascular complications during noncardiac surgery [13]. It takes into account six independent predictive factors of complications, and it is a useful tool in risk stratification [13,14]. The severe postoperative pain score is a preoperative assessment of pain caused by the procedure based on a patient's previous history.…”
Section: Data Sourcementioning
confidence: 99%